Soil carbon and nitrogen in silicate agromineral-managed pasture: a seven-year study in the Cerrado - Silva, Priscila Brelaz da; Carvalho, Arminda Moreira de; Junqueira, Ana Maria Resende; Soares, João Paulo Guimarães; Sá, Marcos Aurelio Carolino de; Marchi, Giuliano; Martins, Eder de Souza; Figueiredo, Cícero Célio de; Santos, Luiz Fernando dos; Sousa, Thais Rodrigues de; Oliveira, Alexsandra Duarte de (Pesquisa Agropecuaria Brasileira, 2025)
The objective of this work was to investigate the long-term effect of the silicate agrominerals ‒ basalt, biotite schist, and kamafugite ‒, as well as of potassium chloride fertilizer on soil carbon (C) and nitrogen (N) contents in pasture systems cultivated with Urochloa brizantha ’BRS Paiaguás’, in the Brazilian Cerrado biome. The evaluated parameters were soil C and N stocks, organic matter fractions, and chemical and physical attributes. No significant differences were observed across treatments for C and N stocks. The total organic carbon (TOC) content of kamafugite and basalt was 15.56 g kg-¹ and 8.21 g kg-1, respectively, which were not significant. TOC correlated positively with the biological soil quality index and nutrient cycling. The particulate organic carbon fraction contributed to carbon retention near the surface, accounting for approximately 50% of C, due to biomass input and microbial activity. Micronutrient levels varied among treatments, and kamafugite showed the highest concentrations. Soil correction and fertilization applied across all treatments, before the application of silicate agrominerals, limited the isolation of agromineral effects. The study underscores the need of undertaking extended research on silicate agrominerals in chronosequences, particularly regarding nutrient dynamics and C stabilization in tropical soils.